The impact of guests’ satisfaction on hotels’ revenue pestana collection hotels analysis - Cavaco, Marta Sofia de Almeida Pimentel (2021)
This project was carried out with the purpose of studying if there is a statistical relationship between Pestana Collection Guests’ satisfaction database and the Pestana Collection Hotels' revenue model. Understanding Guests’ satisfaction about each service and correlating it with the hotel revenues will allow the creation of strategies that captivate even more Guests. This information will be helpful to support a revenue strategy for the new luxury and historical five star Pestana Collection Amsterdam Riverside Hotel, which will open in January 2018.